Analisis Kepastian Hukum atas Perubahan Akta Kepengurusan Koperasi yang Dilakukan tanpa Musyawarah Rapat Anggota (Studi pada Koperasi Bintang Laot di Peureulak Aceh Timur) - Muhammad Imam Mirza; hasim purba; mahmul Seregar (Jurnal Hukum Lex Generalis, 2025)
Legal certainty regarding amendments to the management deed of Bintang Laot Cooperative conducted without the Annual Members' Meeting (RAT) becomes the focus of this study. Unilateral changes using allegedly falsified documents and notarized without proper verification have caused internal conflicts, suspension of economic activities, and legal uncertainty. These actions fulfill the elements of unlawful acts as stipulated in Article 1365 of the Civil Code. Legal remedies such as summons, civil lawsuits, and criminal reports have been pursued to restore legality. This case demonstrates weak notarial supervision and legal protection for cooperatives, necessitating more stringent regulatory reforms.